For Whom the Consumer Price Index Tolls: Reporting of Road Pricing in the consumer expenditure survey. Issue 1 (January 2015) - Peters, Jonathan; King, David A.; Gordon, Cameron; Santiago, Nora Tabori
User fees have long been seen as an efficient financing mechanism because beneficiaries of services pay for the benefits received. This point of view is especially applicable to public services with commercial aspects and in situations for which links between consumption and price are relatively easy to make. However, road pricing, such as tolls, can be very high and important to local price levels. This paper examines the way in which expenditures on tolls are tracked and measured in the United States through the consumer expenditure survey (CES) run by the U.S. Bureau of Labor Statistics. The paper describes the CES and its methods, both generally and for tolls and road charges specifically, and compares those with estimates of U.S. tolls from other sources and from some micro-data the authors have compiled for the New York metropolitan area. The results suggest that the current CES underestimates consumer toll expenditures. Because the CES is a key background input into the consumer price index, the paper argues that flow-on effects continue through to measurement of U.S. inflation and gross domestic product as well.